A Simple and Efficient Protocol for the Synthesis of 3,4-Disubstituted Isoxazol-5(4H)-Ones Catalyzed by Succinic Acid Using Water as Green Reaction Medium - Ghogare, Ramesh S.; Patankar-Jain, Kalpana; Momin, Sana A. H. (Letters in Organic Chemistry, 2021)
A simple and efficient protocol has been established to the synthesis of 3,4-disubstituted isoxazol-5(4H)-ones via Knoevenagel condensation reaction. In this synthesis, succinic acid was used as an inexpensive catalyst and water as a green reaction medium. This method is useful for the preparat ion of various derivatives of 3,4-disubstituted isoxazol-5(4H)-ones in excellent yields.
Keywords: Succinic acid